2004
DOI: 10.1111/j.0886-0440.2004.04004.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Replacement Therapy for Acute Renal Failure After Cardiac Surgery

Abstract: Recognition of ARF and early beginning of the CVVHDF are extremely important. The sooner the ARF after surgery is recognized and CVVHDF is performed, the higher the likelihood of the reduction of the hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(104 citation statements)
references
References 16 publications
5
94
1
4
Order By: Relevance
“…In this study, the door-to-dialysis time was significantly shorter in the PaDD group than in the DAdD group. Studies have shown that door-to-dialysis time is associated with the degree of azotemia and with mortality (11,12,20). Hemodynamic stability was maintained during SLED treatments in both groups.…”
Section: Discussionmentioning
confidence: 89%
“…In this study, the door-to-dialysis time was significantly shorter in the PaDD group than in the DAdD group. Studies have shown that door-to-dialysis time is associated with the degree of azotemia and with mortality (11,12,20). Hemodynamic stability was maintained during SLED treatments in both groups.…”
Section: Discussionmentioning
confidence: 89%
“…Whether early dialysis can improve the uremic milieu of AKI and improve outcomes is unknown. Although a number of studies suggest that early initiation of dialysis may improve mortality in patients with AKI, [36][37][38][39] this remains an area of uncertainty and controversy.…”
Section: Discussionmentioning
confidence: 99%
“…It must also be clearly stated that the traditional indications for timing of RRT in relatively stable patients with isolated acute oliguric renal failure as a single organ system failure not be applied to critically ill patients with AKI as a component of multiple organ failure. In addition, there is a growing body of evidence that fluid overload as a result of AKI contributes significantly to mortality and morbidity and that control of volume status with continuous renal replacement therapy (CRRT) can improve outcomes, especially in pediatric AKI and following cardiac surgery (11)(12)(13)(14)(15). A pH cutoff of 7.15 was chosen in parallel to the Surviving Sepsis Campaign guidelines (16).…”
Section: Parametersmentioning
confidence: 99%
“…There is no consensus on the exact indications for RRT in terms of BUN levels or RIFLE/ AKI staging, although there has been a trend in clinical practice toward earlier RRT in the critically ill. Indeed, a small number of studies suggest that earlier initiation is associated with improved AKI outcome in critically ill patients (14,15,19,20).…”
Section: Current Levels Of Evidence For Use Of Rrt In Akimentioning
confidence: 99%
See 1 more Smart Citation